2021
DOI: 10.21608/ejabf.2021.170055
|View full text |Cite
|
Sign up to set email alerts
|

Is the consumption of Tilapia zillii and Clarias gariepinus from Edku Lake (Egypt) safe for humans: a physiological and biochemical study

Abstract: Edku Lake Proximate body Human risk assessmentThe Egyptian government seeks to develop the northern wetlands, including Edku Lake in El Beheira Governorate, to enhance the physiological functions of fish, and thus, improve their quality and promote their products. Therefore, this study was performed on the two cheapest fish species Tilapia zillii and Clarias gariepinus in the Egyptian market, by studying proximate body composition, antioxidant enzyme activity, and bioaccumulation of five trace elements. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In Buriganga River and adjacent canals of Hazaribagh, Dhaka, Islam et al (2014) recorded that As was found in the ranges of 0.62 to 0.71 mg/kg ww. In Egypt, As concentrations in tilapia zillii and C. gariepinus muscles ranged from 1.43 ± 0.17 to 1.54 ± 0.14 μg/g on average (Abdel-Kader, et al 2021). The values published in the literature were frequently lower than the results of this study Cadmium is a harmful trace metal found in high amounts in fish species (Türkmen et al, 2009).…”
Section: Accumulation Of Trace Elementsmentioning
confidence: 99%
“…In Buriganga River and adjacent canals of Hazaribagh, Dhaka, Islam et al (2014) recorded that As was found in the ranges of 0.62 to 0.71 mg/kg ww. In Egypt, As concentrations in tilapia zillii and C. gariepinus muscles ranged from 1.43 ± 0.17 to 1.54 ± 0.14 μg/g on average (Abdel-Kader, et al 2021). The values published in the literature were frequently lower than the results of this study Cadmium is a harmful trace metal found in high amounts in fish species (Türkmen et al, 2009).…”
Section: Accumulation Of Trace Elementsmentioning
confidence: 99%